Say I have three parameters:
m (in cell B2) lambda (in cell B7) mu (in cell B8)
where I can easily calculate
rho = lambda/(m*mu) (in cell B10)
I now want to calculate
p0 = 1/(1 + (m * rho)^m/(m!*(1-rho)) + sum[n=1 to m-1]( (m*rho)^n / n!) )
How do I enter the sum?
(1/(1+(B2 * (B7/(B2*B8)))^B2/(FACT(B2) * (1-(B7/(B2*B8)))) + ???))
note: I’m generating these formulae in bash so I don’t need to use named cells and can re-use the generated formulae by copying the column and changing the parameters for your convenience:
lambda="B7" mu="B8" m="B2" rho="($lambda/($m*$mu))" echo -e "rho =\n\t$rho" p0="(1/(1+($m * $rho)^$m/(FACT($m) * (1-$rho)) + ???))" echo -e "p0 =\n\t$p0"